Fitting in or Feeling Excluded: The Experiences of High School Students with Visual Impairments. (May 2018) - Jessup, Glenda; Bundy, Anita C.; Broom, Alex; Hancock, Nicola
Introduction: This study compares the experiences of high school students with visual impairments (that is, those who are blind or have low vision) in and out of school. Methods: Twelve visually impaired high school students completed the same in-the-moment survey seven times daily for seven consecutive days. The frequencies of their activities, interactions, and ratings of internal variables (fitting in, acceptance, loneliness, and enjoyment) were compared across three contexts: home, school, and other (neither home nor school) contexts. Results: Participants spent much of their time out of school alone at home. They rated leisure and structured recreation in "other" locations as their most enjoyable activities. Doing nothing at school was the least positively rated activity. Participants fitted in significantly less and felt significantly less accepted at school than elsewhere. A large proportion of school interactions involved receiving help; few involved giving help. Participants with additional disabilities reported more school social challenges than their peers who were only visually impaired. Discussion and implications for practitioners: This study highlights the subjective dimensions of choice in everyday life. The social impact of doing nothing at school provides an imperative for staff members to ensure that adolescents with visual impairments can participate in lessons. Staff may also need to facilitate opportunities for these students to reciprocate with peers. Adolescents with visual impairments highly value activities with friends out of home and, as with most adolescents, may need to lean on their families for assistance in this area until they can participate in such activities independently.